Social Enterprise and Taxation Policy: A Systematic Literature Review - Mohd Rizal Palil; Ida Suriya Ismail; Nor Hazila Mohd Zain; Allif Anwar Abu Bakar (BESTUUR, 2021)
Malaysia is likely to introduce new laws on social enterprises of taxation. However, the important questions are whether the said laws are adequate. This study explores previous research on social enterprises and taxation to gain a further understanding through a systematic literature review on social enterprises and taxation from the Malaysian perspective. This is normative legal research. The data was gathered through library research which consisted of numerous publications. This study concludes that tax and social enterprises, perhaps due to the different economic structures in each country, result in taxation being slightly discussed by previous scholars. Nevertheless, we clearly define social enterprises from different perspectives, including the characteristics present in social enterprises. Moreover, the perspective regarding tax relief for social enterprises in Malaysia has been highlighted. Although Malaysia has introduced a new policy to support its social enterprises with Social Enterprise Accreditation, a more significant regulatory or tax incentives approach is needed to support social enterprises in Malaysia.